Hypoalbuminemia Predicts Adverse Events following Unicompartmental Knee Arthroplasty - Hur, Edward S.; Bohl, Daniel D.; Della Valle, Craig J.; Villalobos, Felipe; Gerlinger, Tad L. (The Journal of Knee Surgery, 2021)
Hypoalbuminemia is a potentially modifiable risk factor associated with adverse events following total knee arthroplasty. The present study aimed to evaluate whether hypoalbuminemia similarly predisposes to adverse events following unicompartmental knee arthroplasty (UKA). Patients who underwent UKA during 2006–2018 were identified through the American College of Surgeons National Surgical Quality Improvement Program. Only patients with preoperative serum albumin concentration were included. Outcomes were compared between patients with and without hypoalbuminemia (serum albumin concentration < 3.5 g/dL). All associations were adjusted for demographic, comorbidity, and laboratory differences between populations. A total of 11,342 patients were identified, of whom 6,049 (53.3%) had preoperative serum albumin laboratory values available for analysis. After adjustment for potential confounders, patients with hypoalbuminemia had a greater than 2-fold increased probability for occurrence of any complication (7.02% vs. 2.23%, p = 0.009) and a 4-fold increased probability of receiving a blood transfusion (1.81% vs. 0.25%, p = 0.045). Among procedures performed as inpatients, mean postoperative length of stay (LOS) was longer in patients with hypoalbuminemia (2.2 vs. 1.8 days; p = 0.031). Hypoalbuminemia is independently associated with complications and increased LOS following UKA and a marker for patients at higher risk of postoperative complications. Patients should be screened for hypoalbuminemia and nutritional deficiencies addressed prior to UKA.
Keywords: hypoalbuminemia; malnutrition; unicompartmental knee arthroplasty; adverse events